Research on Damage Characteristics of Brick Masonry under Explosion Load - Jifeng Wei; Zhixin Du; Yonghui Zheng; Oundavong Ounhueane (Shock and Vibration)
As the main structural component of partition wall or load-bearing wall, brick masonry has been widely used in construction engineering. However, brick and mortar are all brittle materials prone to crack. Nowadays, fireworks, gas stoves, high-pressure vessels, and other military explosives may explode to damage nearby structures. Many explosion casualties had shown that the load-bearing capacity of brick masonry decreased dramatically and cracks or fragments appeared. Previous studies mainly focused on noncontact explosion in which shock wave is the main damage element. In fact, the response and damage effect of brick masonry wall under contact explosion are more complex, which attracts more attention now. In order to explore the damage characteristics of brick masonry under explosion load, a series of simulations and verification experiments are conducted. RHT and MO granular material models are introduced to describe the behaviour of brick and masonry, respectively, in simulation. The combination effect of front compressive wave and back tensile wave are main factors influencing the breakage of masonry wall. The experimental results are well in accordance with the simulation results. The front cross section dimension of crater is closely related to the radius of spherical explosive charge. A power function predictive model is developed to express the relationship between the radius of hole and the radius of explosive. Furthermore, with increasing the quantity of explosive charge, the number and ejection velocity of fragments are all increased. The relationship between maximum ejection velocity and the quantity of explosive also can be expressed as a power function model.